Crystal structure of SARS-CoV-2 main protease in complex with the natural product inhibitor shikonin illuminates a unique binding mode - Li, Jian; Zhou, Xuelan; Zhang, Yan; Zhong, Fanglin; Lin, Cheng; McCormick, Peter J.; Jiang, Feng; Luo, Jun; Zhou, Huan; Wang, Qisheng; Fu, Yang; Duan, Jingjing; et al. (Science bulletin (Beijing), 2021)
[Display omitted]